Investigating the effect of speech tools (Video Media (TV)) and internet on the consumers purchasing behavior in developed countries - Mazhari, Mohammad Yaser (EuroJournals Publishing, Inc., 2013)
The contemporary competitive environment, drawing consumers is challenging and quite difficult to be attained. One remarkable method for marketers to attract customers is through advertisement and its allied tools. This study intends to find out the level of the influence of advertising tools, such as the speech tool (video Media (TV)) and Internet, on consumers’ purchasing behavior with regards to the purchase of detergents in Kuala Lumpur (KL) in Malaysia. Likewise, delves into the comparative influences of advertising tools between the two advertising tools. There are 384 costumer-respondents in these studies who are residents of KL. The instrument utilized in data gathering was through a questionnaire survey and the data were analyzed based on Friedman and One-Sample Test model. The findings revealed that there exists significant difference between the two advertising instruments (speech tools (video Media (TV) and Internet) which have been used in this research. Results show that the Internet medium is more effective on influencing consumers’ behavior on purchasing detergent than the TV.